Faktor Pengaruh Penerapan Keselamatan dan Kesehatan Kerja (K3) terhadap Kecelakaan Kerja Proyek Kontruksi Well Development di PT. Pertamina Hulu Rokan Petapahan Riau - Ayup, Yufirman; Carlo, Nasfryzal; Utama, Lusi (Jurnal Talenta Sipil, 2025)
The development of construction projects in the era of globalization is not free from danger. Risk control for occupational safety and health (K3) is needed to minimize work accidents. Based on work accident data in 2023, three workers died in a waste tank or container in the PT Pertamina Hulu Rokan (PHR) area. They were found floating in the waste tank dead. Based on the investigation and investigation of the incident, it was found that the workers did not comply with the Standard Operating Procedures (SOP) of Occupational Safety and Health (K3). Based on this incident, the purpose of this study was conducted to determine how much influence the application of K3 in PT Pertamina (Persero) by identifying factors influencing the application of occupational safety and health (K3) to work accidents in the well development construction project at PT Pertamina upstream Rokan. Petapahan Riau. The method used is a survey method using a questionnaire instrument. Determination of the number of respondents based on the slovin equation. The questionnaire used a Likert scale and was distributed directly to 128 respondents. The classification of respondents is from Pt. Pertamina Hulu Rokan Petapahan Riau (PHR), namely, Representative, Project Consultant, Project Manager, HSE Manager, Construction Superintendent, HSE Superintendent, Construction Supervisor, and HSE Supervisor. The questionnaire results were statistically analyzed using SPSS. It was found that 3 main factors influence the application of occupational safety and health (OHS) on work accidents, namely, the fulfillment factor of laws and regulations, the OHS policy commitment factor, and the human factor, the dependent factor in this study is work accidents. The human factor is the most influential factor on the occurrence of work accidents, with the highest influence factor (t count) of 4.680.